Construction, molecular characterization, and safety assessment of purB mutant of Salmonella Gallinarum - Mukhtar, Masham; Ghafoor, Aamir; McClelland, Michael; Akhtar, Fareeha; Rasheed, Muhammad Adil (Frontiers in Microbiology, 2024)
This study involves the development and molecular characterization of the isogenic markerless knockout mutant SG ΔpurB, a genetically engineered live attenuated strain aimed at controlling Salmonella Gallinarum (SG) infection in poultry. The mutant was generated by deleting the purB gene using λ-Red recombination technology, impairing adenylosuccinate lyase, necessary for purine biosynthesis. An 1,180 bp deletion was engineered within the purB gene, leaving a residual 298 bp genomic scar resulting in a purine auxotrophic mutant. Phenotypically, SG ΔpurB showed a 66.5% reduction in growth in LB broth compared to the wild-type strain and failed to grow in minimal media without adenosine. Growth was restored to near wild-type levels with 0.3 mM adenosine supplementation, demonstrating the strain’s conditional attenuation. In vivo pathogenicity assessments revealed that oral inoculation of SG ΔpurB into 3-day-old chickens at a dose of 2 × 108 CFU resulted in zero mortality, compared to an 80% mortality rate in chickens challenged with the wild-type strain. The SG ΔpurB strain exhibited significantly reduced clinical signs and lesion scores, with clinical sign scores dropping from 2.5/3 with the wild-type to 0.4/3 with the ΔpurB mutant, and lesion scores decreasing from 2.9/3 to 0.3/3. Additionally, the mutant was efficiently cleared from liver and spleen tissues by 14 days post-inoculation, unlike the wild-type strain, which persisted until the experiment’s end on day 21. The SG ΔpurB mutant shows potential as a safe alternative for preventing fowl typhoid, highlighting the promise of targeted genetic attenuation in developing effective vaccines for poultry diseases.